The Role of the Law in the Guano Era - Pásara, Luis (1970)
The purpose of this paper is to analyze the role of law in the period of guano exploitation in Peru between 1840 and 1875. To that extent, the author points out that law had a social impact during the economic boom of guano by acting as a means to regulate the external commercialization of this natural fertilizer. In this way, national regulations legitimized internal domination by favoring the interests of a small dominant group whose economic and political power benefited from the subordination of the majority. In addition, the author explains how such subordination not only facilitated but also increased the exploitation of the less favored sectors. The article concludes by pointing out that instead of contributing to national development, the role played by the law at that time ended up having a negative impact on the country, since it only favored the exploitation of the central economy at the expense of the peripheral one, thus aggravating the existing inequalities.